Earnings Management and New Listings: Evidence from Vietnam - Anh Huu Nguyen (Universiti Sains Malaysia, 2021)
Earnings management around corporate events has been widely discussed in literature review which has shown mixed results. Furthermore, prior studies have extensively focused on earnings management around initial public offerings (IPOs) and seasoned equity offerings (SEOs), while less attention has been given to the listing event. Another motivation comes from the context of the undeveloped market. While earnings management has been widely discussed in developed countries, it is still limited in emerging countries in general and in Vietnam in particular, due to the lack of research on this phenomenon and the unique institutional feature and pre-listing profit requirement in Vietnam’s stock market. This research is conducted to investigate the earnings management behaviour around listing event in Vietnam. The sample of this study consists of financial data from 189 newly listed companies on the Ho Chi Minh City Stock Exchange (HOSE) for the period of 2009–2017. Four cross-sectional models were used to estimate earnings management, including two total accruals-based models and two current accruals-based models. This research makes important contributions to the body of literature on Vietnam’s stock market. First, this study provides empirical evidence suggesting a greater positive earnings management practice of newly listed firms in current accrual models than those in total accrual models. Second, the results from both parametric and non-parametric test statistics show that HOSE-listed firms present higher levels of earnings management in the year prior to the listing than those in post-listing year and two subsequent years after listing. Finally, new listing requirements in 2012 require the company’s return on equity (ROE) in the most recent year to be at least 5%. However, the paper finds no evidence to suggest that relative to all newly listed firms after the new profit requirement exhibit greater positive earnings management than that of firms listed before the change in pre-listing year.